Online teaching in Spain after the pandemic: Challenges and opportunities in formal education - Bárcena-Toyos, Patricia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The present study examined teachers’ perceptions about their teaching practices and use of ICTs before and after the COVID-19 pandemic, by means of two questionnaires. Results showed a general increase in the use of ICTs, although it was less marked in those teachers who used them sporadically. Furthermore, teachers perceived an increase in students’ motivation and an improvement of academic results in the school year 2020/21. Teachers also noted the difficulties they found to follow the curriculum, to evaluate students and to solve disruptive behaviors online.